2017
DOI: 10.1002/ece3.3225
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of mating decisions in stalk‐eyed flies

Abstract: All too often, studies of sexual selection focus exclusively on the responses in one sex, on single traits, typically those that are exaggerated and strongly sexually dimorphic. They ignore a range of less obvious traits and behavior, in both sexes, involved in the interactions leading to mate choice. To remedy this imbalance, we analyze a textbook example of sexual selection in the stalk‐eyed fly (Diasemopsis meigenii). We studied several traits in a novel, insightful, and efficient experimental design, exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…3B) was measured, and its correlation with eye span was examined (coefficient of determination = 0.44, P value = 0.0018). The results showed that eye span and reproductive capacity were correlated in both sexes, as shown in previous studies in other stalk-eyed fly species 15,19,25,26 .…”
Section: Hypothesis 1: Eye Span Acts As An Honest Signal To Inform Opsupporting
confidence: 88%
“…3B) was measured, and its correlation with eye span was examined (coefficient of determination = 0.44, P value = 0.0018). The results showed that eye span and reproductive capacity were correlated in both sexes, as shown in previous studies in other stalk-eyed fly species 15,19,25,26 .…”
Section: Hypothesis 1: Eye Span Acts As An Honest Signal To Inform Opsupporting
confidence: 88%
“…If some degree of stress is typical of ecological conditions in nature, sexual selection could often be stronger than currently estimated from laboratory experiments—usually carried out under low stress conditions of ad libitum food and constant temperature and without predators, parasites or ecological competitors. We note that our experimentation used stress from a unimodal environment variable (food availability), controlling all other physical and biotic factors, and that we used a simple measure of male signalling, leaving aside other, more subtle aspects of male behaviour used in female evaluation of their partners (Chapman et al, ). Thus, the majority of environments probably lie between the low and high stress regimes, which is consistent with the considerable range in eyespan observed among wild‐caught stalk‐eyed flies (Cotton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…After eclosion, flies of each cross were collected and frozen at −20°C. All males were measured for eyespan (the distance between the outermost tips of the eyes, Chapman et al, 2017;David et al, 1998) and thorax (the distance between the centre of the most posterior point of the head to the joint between the meta-thoracic legs and the thorax, Meade et al, 2017;Rogers, Denniff, Chapman, Fowler, & Pomiankowski, 2008) to a tolerance of 0.01 mm, using a video camera mounted on a monocular microscope and imagej image capture software v.1.46 (Schneider, Rasband, & Eliceiri, 2012). The repeatability of these morphological trait measurements is very high at >99% (David et al, 1998).…”
Section: Adult Morphologymentioning
confidence: 99%
“…While there was no difference in the preference of SR and ST males, we did find that eyespan affected male preference for large females, with large eyespan males showing the strongest preference and small eyespan males exhibiting no preference at all. Vision is the dominant sensory mode for assessment of potential mates in stalk-eyed flies (Chapman et al 2005; Chapman et al 2017), and both stereoscopic vision and visual acuity are improved as eyespan increases (Burkhardt and de la Motte, 1983; de la Motte and Burkhardt, 1983). It follows that males with larger eyespan will be better able to distinguish differences between females and express stronger preference.…”
Section: Discussionmentioning
confidence: 99%